Intensity-Enhanced Apodization Effect on an Axially Illuminated Circular-Column Particle-Lens; Annalen der Physik; Vol. 530, iss. 2 - Yue Liyang; Bing Yan; Monks J. N. James; Dhama R.; Wang Z. Zengbo; Minin O. V. Oleg Vladilenovich; Minin I. V. Igor Vladilenovich (2018, 2018)
Title screen